Bibliometric Analysis of Intelligence and Espionage Activities in Indonesia - Syahputra, Alfin Reza (Universitas Nahdlatul Ulama Blitar, 2024)
This research examines various strategic intelligence research over the last 10 years. This research adopts a qualitative method based on the results of a bibliometric analysis review of various literature. The literature is obtained from Google Scholar with the help of the Publish or Perish program. The literature search was limited to the year 2015 to 2023 with selected keywords and titles, including the keywords